1999
DOI: 10.1091/mbc.10.7.2163
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies with Purified Components Reveal Signal Recognition Particle (SRP) and SecA/SecB as Constituents of Two Independent Protein-targeting Pathways ofEscherichia coli

Abstract: The molecular requirements for the translocation of secretory proteins across, and the integration of membrane proteins into, the plasma membrane of Escherichia coli were compared. This was achieved in a novel cell-free system from E. coli which, by extensive subfractionation, was simultaneously rendered deficient in SecA/SecB and the signal recognition particle (SRP) components, Ffh (P48), 4.5S RNA, and FtsY. The integration of two membrane proteins into inside-out plasma membrane vesicles of E. coli required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
214
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(228 citation statements)
references
References 48 publications
13
214
0
1
Order By: Relevance
“…6). Multiple factors render this assay an optimal choice for testing insights from biophysical studies of SRP in a complete targeting reaction: (i) Bacterial SRP and FtsY mediate pPL targeting as efficiently as their mammalian homologs despite the heterologous nature of this assay (61), highlighting the remarkable conservation of the SRP pathway; (ii) wheat germ extract is devoid of endogenous SRP and potential SRP regulators that may serve redundant functions as TF, which allows the effect of TF to be most readily unmasked; (iii) the microsomal membrane has much higher cotranslational translocation activity than bacterial membrane vesicles (62)(63)(64), so that the output of the assay is not limited by the downstream translocation steps; and (iv) rapid cleavage of signal sequences by signal peptidase allows both the premature and mature proteins to be quantified, providing the most accurate quantification of targeting efficiency; analogous readouts are not available with bacterial membrane vesicles. Finally, the Sec translocon has a more relaxed specificity than SRP and translocates both cotranslational and posttranslationally targeted substrates (65); thus, the overall assay reports on the more stringent substrate selection by the SRP pathway.…”
Section: Resultsmentioning
confidence: 99%
“…6). Multiple factors render this assay an optimal choice for testing insights from biophysical studies of SRP in a complete targeting reaction: (i) Bacterial SRP and FtsY mediate pPL targeting as efficiently as their mammalian homologs despite the heterologous nature of this assay (61), highlighting the remarkable conservation of the SRP pathway; (ii) wheat germ extract is devoid of endogenous SRP and potential SRP regulators that may serve redundant functions as TF, which allows the effect of TF to be most readily unmasked; (iii) the microsomal membrane has much higher cotranslational translocation activity than bacterial membrane vesicles (62)(63)(64), so that the output of the assay is not limited by the downstream translocation steps; and (iv) rapid cleavage of signal sequences by signal peptidase allows both the premature and mature proteins to be quantified, providing the most accurate quantification of targeting efficiency; analogous readouts are not available with bacterial membrane vesicles. Finally, the Sec translocon has a more relaxed specificity than SRP and translocates both cotranslational and posttranslationally targeted substrates (65); thus, the overall assay reports on the more stringent substrate selection by the SRP pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This genetic screening strategy suggested that only membrane proteins serve as SRP substrates. Furthermore, in vitro studies with puri¢ed components revealed that membrane proteins required SRP components, but not SecA/SecB, for membrane integration, whereas secretory proteins required SecA/SecB, but not SRP components, for translocation [5]. These latter studies suggest that most E. coli secretory proteins can utilize the SRP-independent pathway with high e¤ciency.…”
Section: Introductionmentioning
confidence: 95%
“…Efficient integration into membranes was observed, even if the SecYEG translocon was absent, when MtlA was in vitro synthesized with liposomes composed of Escherichia coli phospholipids (7). This observation is not compatible at all with the in vitro results obtained using INV prepared from mutant strains (12,13); therefore, it must be an artifact owing to the artificial membrane system (7). Nonetheless, it should reflect membrane integration because it was stimulated by SRP/SR, and resistant against urea and high-salt extraction.…”
Section: Spontaneous Insertion and Diacylglycerol (Dag)mentioning
confidence: 99%
“…In the case of MtlA (mannitol permease) with six TMs, an MPF of ∼30 kDa is generated upon membrane integration (10,11). The in vitro system involving INV prepared from mutant strains demonstrated that MtlA is targeted to a membrane by SRP and SR, followed by integration into the membrane at the SecYEG translocon; that is, it is Sec dependent (12,13). Efficient integration into membranes was observed, even if the SecYEG translocon was absent, when MtlA was in vitro synthesized with liposomes composed of Escherichia coli phospholipids (7).…”
Section: Spontaneous Insertion and Diacylglycerol (Dag)mentioning
confidence: 99%
See 1 more Smart Citation